Threshold dynamics of a time periodic and two–group epidemic model with distributed delay - Lin Zhao; Zhi-Cheng Wang; Liang Zhang (Mathematical Biosciences and Engineering)
In this paper, a time periodic and two–group reaction–diffusion epidemic model with distributed delay is proposed and investigated. We firstly introduce the basic reproduction number $R_0$ for the model via the next generation operator method. We then establish the threshold dynamics of the model in terms of $R_0$, that is, the disease is uniformly persistent if $R_0 \gt 1$, while the disease goes to extinction if $R_0 \lt 1$. Finally, we study the global dynamics for the model in a special case when all the coefficients are independent of spatio–temporal variables.